All World Media: a new business model (cases A and B). Issue 3 (10th September 2015) - Kerem, Katri; Sternad, Dietmar
Abstract : Synopsis: This failure case study tells the story of All World Media, a start-up offering internet-based media planning and buying tool created by ambitious Estonian entrepreneurs in 2011. A few years earlier the two founders had come up with an idea that in their opinion would revolutionize the process of media planning and buying for advertisers. They had noticed that the industry worked in an intransparent and inefficient way. Based on their own extensive experience in various internet ventures and following first consultations with key industry players they were confident that the market was ready for a self-service online media marketplace. Research methodology: The (A) case focusses on the initial business idea and on the events before the launch of the internet platform. The case includes the entrepreneurs' concept, the main contents of the business plan, and the operational steps until the launch of the service on the market. The (B) case outlines the events after the launch of the online service, analyzes the possible reasons for the failure of the original business model and discusses potential strategic alternatives that are still open for the entrepreneurs. Relevant courses and levels: The two-case sequence can be used for a 90-minutes session in marketing, entrepreneurship or strategic management courses in graduate and executive programs. The case is accompanied by an instructor's manual which also includes suggested assignment questions and proposed session plan.